MENINGKATKAN KEMAMPUAN MEMBILANG MELALUI PERMAINAN ULAR TANGGA BAGI ANAK TUNARUNGU (Single Subject Research Kelas D1/B di SLB Amal Bhakti Sicincin) - Kurnia Milawati Nurasmi (Universitas Negeri Padang, 2012)
This reseach is base on the problem that happened on trap student grat DI/B SLB Amal Bakti who have difficulties in accounting step by step. from the result of a student who is less in acounting step by step since in acounting a student is not fluent, because the number that she says is not sincronize with the number itself. Beside that she is easy to be bored. This research uses experiment aproach in the form of Single Subjek Research (SSR) by the design A –B. The subject of this reseach are the deaf students. The result of this research show us that the ability of counting of deaf increase. By baseline condition, the X deaf can count only once 10 % but when it is in intervention condition, they can count step by step 8 times (80 %), this situation happened on the sixth and seventh and also eight of observation based on the research can be conclude that snake ladder game can increas the ability of deaf students at SLB Amal Bakti Sicincin. From this research , if will have function for the students, teachers, parent and research herself. And then it can be have to continue this game to improve the ability of the deaf in counting.